Pemberian Makanan Tambahan (PMT) Berbahan Pangan Lokal Terhadap Kenaikan Berat Badan pada Balita Gizi Kurang : Studi Kasus Puskesmas Grogol Kabupaten Sukoharjo - Puput Fitria Erli Ningtyas; Muwakhidah Muwakhidah; Asti Nugrahani (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Undernutrition in toddlers remains a pressing issue in improving public health. One potential and contextually relevant intervention is the provision of supplementary feeding (PMT) using locally sourced foods. This case study aimed to evaluate changes in the nutritional status of an undernourished toddler following a 14-day intervention with local food-based PMT. The study involved a 15-month-old toddler diagnosed with underweight and stunting. The intervention consisted of high-energy and high-protein snacks made from local ingredients, provided twice daily. Monitoring was conducted on body weight and height on day 0, day 7, and day 14. In addition, nutrition education and counseling were given to the toddler's parents. The results showed an increase in body weight from 6.6 kg to 6.95 kg, while height remained unchanged at 69 cm. The weight gain reflects a positive response to the short-term local PMT intervention. Conversely, the static height suggests that longer intervention periods are needed to support improvements in linear growth. Parental education played an important role in enhancing understanding of balanced nutrition practices. This study highlights the importance of comprehensive nutritional interventions that go beyond food provision, integrating family education and environmental improvements to achieve sustainable and optimal outcomes.